Stitching together the conversation - considerations in the design of extended social talk - Vogel, Carl; Spillane, Brendan; Wade, Vincent; Campbell, Nick (My University, 2018)
Spoken interaction mediates much human social and practical activity. Talk is not monolithic in form but rather weaves in and out of different genres. Practical tasks are peppered with lubricating social talk, while casual conversation proceeds in phases of interactive chat and longer almost monologue chunks. There is increasing interest in building applications which enable convincing human-machine spoken or text interactions, not only to facilitate immediate practical tasks but also to build a longer term relationships within which conversation can take place in order to entertain, provide companionship and care, and build a user model which will facilitate future tasks through an ‘always on’ conversational interface. Such applications will require modelling of the different subgenres of talk, and of how these can be convincingly joined to form a coherent ongoing conversation. In this paper we describe our work towards modelling such talk, focussing on theories of casual talk, insights gleaned from human-human corpora, and implications for dialog system design.
9th INTERNATIONAL WORKSHOP ON SPOKEN DIALOGUE SYSTEMS TECHNOLOGY (IWSDS2018)
PUBLISHED
Singapore
Keywords: Digital Engagement; Digital Humanities; Computational Linguistics; Computational linguistics; DIALOG; Discourse & Dialogue; computational linguistics; Communication